The relationship between the ketuk tilu dance and the jaipongan dance - Agustina, Wina Resky (Universitas Suryakancana, 2024)
The Ketuk Tilu Dance as a typical West Javanese folk dance which initially functioned as a ceremonial dance welcoming the rice harvest, and in its development has changed its function to become an entertainment and spectacle dance that usually appears on night market events, celebrations and so on. In the 1980s came the Jaipongan Dance created by Gugum Gumbira. So that makes dancers become more active. The appearance of the dance by Gugum Gumbira was originally called “Ketuk Tilu Development